Model Skrining Tumbuh Kembang Balita berbasis Pemberdayaan Guru PAUD - Fuadah Ashri Nurfurqoni (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2018)
The enthusiasm of people to come to Posyandu diminishing that is caused busyness of parents, as well as the activities of children/toddlers itself, follow the ECD (Early Childhood Education). That requires an activity that can facilitate the right to health and education of children. Among the screening model of growth through empowerment-based Early Education Childhood teachers. Activities carried out in 2015 through the training of 13 teachers from two schools of early childhood education, teachers are given the skills to detect proper growth and development of students, this activity is also expected to initiate a partnership between the manager of early childhood with the clinic. Training begins with a pretest and proceeds with the mentoring phase. After those early childhood teachers screened independently growth was accompanied by a team of community service. Screening is done every month of growth while screening Indonesia Economic carried 2 times with an interval of 6 months. Furthermore, at the final stage will be carried out post-test that shows there is an increase in the skills and knowledge of teachers in child development screening. From the results of screening known is 1 student who has developmental disorders and 8 people with dubious results. Students who experience irregularities ascribed to the Developmental Clinic for further intervention. While students who have dubious results do the tests in 2 weeks later with 6 results according to the development, while 2 others in need of stimulation for fine motoric independence and socialization. Teacher Empowerment kindergarten / early childhood effective enough to support the implementation of developmental screening of preschool children. So that this activity should be continued in early childhood more Keywords: Screening, Growing, Flower, Toddler, Teacher, ECD